Study of scale formation due to incompatible water - Merdhah, Amer Badr; Mohd. Yassin, Abu Azam (Penerbit UTM Press, 2008)
In the oil field, due to the extensive use of water injection for oil displacement and pressure maintenance, many reservoirs experience the problem of scale deposition when injection water begins to break through. Experience in the oil industry has indicated that many oil wells have suffered flow restriction because of scale deposition within the oil producing formation matrix and the down-hole equipment, generally in primary, secondary and tertiary oil recovery operation as well as scale deposits in the surface production equipment. This study was conducted to investigate the permeability reduction caused by deposition of calcium, strontium, and barium sulfates in sandstone cores from mixing of injected sea water and formation water that contained high concentration of calcium, barium, and strontium ions at various temperatures (50 - 80 Â°C) and differential pressures (100 - 200 psig). The solubility of common oil field scales formed and how their solubilities were affected by changes in salinity and temperatures (40 - 90 Â°C) were also studied. The morphology and particle size of scaling crystals formed as shown by Scanning Electron Microscopy (SEM) were also presented. The results showed that a large extent of permeability damage caused by calcium, strontium, and barium sulfates that deposited on the rock pore surface. The rock permeability decline indicates the influence of the concentration of calcium, barium, and strontium ions. At higher temperatures, the deposition of CaSO4, and SrSO4 scales increases and the deposition of BaSO4 scale decreases since the solubilities of CaSO4, and SrSO4 scales decreases and the solubility of BaSO4 increases with increasing temperature. The deposition of CaSO4, SrSO4, and BaSO4 scales during flow of injection waters into porous media was shown by Scanning Electron Microscopy (SEM) micrographs.